Comparison of efficacy and safety of preoperative Chemoradiotherapy in locally advanced upper and middle/lower rectal cancer - Huang, Ming-Yii (Radiat Oncol, 2018)
BACKGROUND: We aimed to explore the efficacy and safety profile of preoperative neoadjuvant chemoradiation (NACRT) in locally advanced rectal cancer (LARC) in upper rectum versus middle/lower rectum. METHODS: The study included 173 patients with stage II or III (T2-4b, N0-2b) LARC who underwent NACRT followed by total mesorectal excision (TME) between January 2011 and October 2016. Cox regression, log-rank test, and Kaplan–Meier curves were calculated. RESULTS: Among the 173 patients, 58 had lesions in the upper rectum and 115 patients had lesions in middle/lower rectum. In a median follow-up of 35 months (range, 6–73 months), the 5-year disease-free survival (DFS) and overall survival (OS) were 84% and 88% for the patients with upper rectal cancer and 77% and 68% for those with middle/lower rectal cancer (P = 0.251 and P = 0.058, respectively). The 5-year DFS (P = 0.012) and OS (P = 0.003) were better in the NACRT responders [tumor regression grade (TRG) 0 or 1] compared with nonresponders (TRG 2 or 3). The independent prognostic factor of favorable response to NACRT was the FOLFOX regimen (P = 0.004). CONCLUSIONS: Patients with LARC in the upper rectum who underwent NACRT followed by TME had similar DFS and a trend toward longer OS, compared with those who had middle/lower rectal lesions. Furthermore, FOLFOX may yield superior results than fluoropyrimidine based regimen during NACRT. NACRT might be an alternative option for patients with LARC in the upper rectum as it has a favorable pathological complete response rate and comparable clinical outcomes when compared with patients with LARC in middle/lower rectum.